Acute Coronary Syndrome and patient behavior factors in overcoming the event of chest pain in pre hospital phase - Cipto Susilo; Mochammad Bagus Qomaruddin; Mellani Puji Fahrera (Journal of Public Health Research, 2020)
Background: Acute coronary syndrome (ACS) is a complex disease induced by thrombosis, which causes unstable angina (UA), acute myocardial infarction (AMI) or sudden cardiac death. It is important to rapidly detect the presence of chest pain to conduct the pre-hospital phase. This study aims to analyze the behavioral factors of patients suffering from ACS in overcoming the incidence of chest pain in the prehospital phase. Design and Methods: The consecutive sampling technique and cross-sectional method were used to obtain data from a sample of 110 outpatient respondents at the Community- Integrated Health Center. Results: After the logistic regression test, a significant relationship was found between the occurrence of chest pain (Pvalue = 0.040), with compressive behavior factors, buying over the counter drugs (P-value = 0.001), massaging and rubbing with oil (P-value = 0.046). Conclusions: In conclusion, the significant behavioral factors associated with ACS sufferers in dealing with the occurrence of chest pain in the pre-hospital phase are due to the act of buying OTC drugs and the habit of massaging or rubbing with oil.